BOT-2 Evaluation of Gender Differences in Upper Limb Coordination among Children 7 to 9 Years Old - Nikola Prvulović; Borko Katanić; Boris Banjević (Lithuanian Sports University, 2022)
Numerous recent studies indicate the significant impact of fundamental motor skills on the psychological and social development of young boys and girls. However, it is not well-known if there are differences between boys and girls aged 7 to 9 in terms of the fundamental development of motor skills. Purpose: The aim of this study is to address the question of the fundamental issues between boys and girls using upper limb coordination evaluated by the Bruininks-Oseretsky test of motor proficiency (BOT-2), including seven sub-scales of measurement. Method: The participants (n=79) were 41 boys and 38 girls aged 7 to 9 years old. BOT-2 test scores were used for upper limb coordination (ULC) differences by gender. Results: The BOT-2 measurements of upper limb coordination show a significant difference in favor of the boys only for 6ULC=7±2.77 relative to 5.66±2.66, (d=.49, ES=.24, p=.03) and 7ULC=2±1.45, relative to 1.32±1.21, (d=.51, ES=.25 p=.02), while for the other tests there are no significant differences. The magnitude of the impact was on the values of the alternate hand dribble, p=.23, while the little effect was achieved for throwing a ball at a target, p=.25. Conclusion: Our results showed that there are no significant differences between boys and girls in terms of the fundamental development of motor skills, indicating a strong biological determinant of homogenous development. Keywords: upper limb coordination, motor skills, sex differences, school children, motor development.